KAJIAN TENTANG KEPUTUSAN PEMBELIAN PRODUK RAMAH LINGKUNGAN DALAM PERSPEKTIF THEORY OF PLANNED BEHAVIOR - Agung Wijaya; Jeni Wulandari; Prasetya Nugeraha (Jurnal Sosial Humaniora, 2020)
This study examines purchasing decisions of green products, viewed from the aspect of consumer preferences and perceptions in the perspective of Theory of Planned Behavior (Ajzen, 1991). A quantitative approach was applied, using a questionnaire to 100 respondents. Data were analyzed using multiple linear regression analysis. The results of the study show that simultaneously, consumer  preferences and perceptions influence purchasing decisions. However, partially, there is no influence of preference on purchasing decisions of green products. This study provides support for further expansion of the theory of planned behavior in the context of enviromental consumerism, as well as practical support for producers, marketers, and public policy makers in encouraging ecosystems of responsible consumption and do not harm the environment.